Impact of regulatory process on telecommunications market performance: Evidence from parametric and non parametric approach - Ahmed Ben Khalifa; Ramzi Ben Slama; Sami Debbichi (International Telecommunications Society (ITS), 2013)
In this paper we explore the impact of regulation; privatization and competition on the both mobile and fixed phone performance, in terms of service quality (network faults) and tariffs in both fix and mobile telecommunication services, using the technique of tow econometric approaches. A parametric approach (Panel Data) and non parametric approach (Matching method). The first, analyze the effect of regulation, privatization and competition on mobile networks performance in terms of quality and tariffs using the interaction effect method in linear model. Our aim is to study the nature of interaction effect between indicators: independence, regulation, competition and privatization on the market performance. The second approach is to correct the inefficiencies of the first estimation and based on propensity score matching (Difference-in-Differences estimations (Heckman et al., 1997, Meyer, 1995)), from 1990 to 2008. Overall, our estimations show a positive relationship between the presence of regulator and tariffs and quality. However, competition has no effect on tariffs. This result allows us to suspect the presence of collusion between competitors and found using the tow approaches.
Keywords: L50; L96; C14; 330; Telecommunications market; Tariffs and Quality Performance; Regulation; Difference-in-Differences